The Descriptive Analysis of Students’ Writing Descriptive Text by Using Picture Word Inductive Model (PWIM) at the Tenth Grade of SMK Swasta Cahaya Lahewa in 2022/2023. - Veronica Victoria Nazara; Elwin Piarawan Zebua; Yaredi Waruwu; Nursayani Maru’ao (LP. Ma'arif Janggan Magetan, 2023)
This research was aimed to analyze the students’ writing competence in descriptive text by using Picture Word Inductive Model (PWIM) at the tenth grade of SMK Swasta Cahaya Lahewa. This research used descriptive research type with PWIM model. The data was students’ writing descriptive text by tenth grade of SMK Swasta Cahaya Lahewa. The instruments that used to collect the data were observation sheet and interview sheet. The data was analyzed by using writing scoring rubric that consist of five main aspects, namely: content, organization, vocabulary, language use, and mechanics. Furthermore, the researcher presented the data with percentage of scoring and described it into a description paragraph. The result of study showed that students’ writing descriptive text by using PWIM had not fulfilled the requirements needed, where the content was (77%), organization was (75%), vocabulary was (86%), language use was (74%), and mechanics was (69%). The percentage showed that the students were difficult to organize the ideas, lack of vocabulary and training when implemented PWIM and also environmental influence such motivation and interest in writing. Based on the results of this research, the researcher concluded that the implementation of PWIM was not appropriate in students’ writing descriptive text because of the low ability of students, particularly at the tenth grade of SMK Swasta Cahaya Lahewa.